Mediating role of enterprise risk management practices between business strategy and SME performance. Issue 2 (4th May 2019) - Rehman, Amin Ur; Anwar, Muhammad
ABSTRACT: Increased competition has highlighted the need for more effective firm level strategies for SMEs to achieve competitive advantage. In fact, SMEs face higher risks in terms of globalization as a result of their limited resources and small size. This study highlights the importance of business strategy in SME performance with the mediating role of enterprise risk management. A structured questionnaire was used to collect data from 327 Pakistani SMEs. The hypotheses are tested using Structural Equation Modeling (SEM) in AMOS. The results indicate that business strategy has a significant influence on SME performance and enterprise risk management. In addition, enterprise risk management partially mediates the relationship between business strategy and SME performance. This study finds that firms with a unique business strategy endorse formal risk management practices which in turn facilitate superior performance in the market. Implications for practices are discussed.